THE ROLE OF ENGLISH EDUCATION TOWARDS STUDENT’S MORALS (At State Vocational High Schools 1 Karawang) - Asep Darojatul Romli; Asep Jamaludin; Sihabudin (JURNAL BUANA PENGABDIAN, 2020)
This research is useful for: a. State School 1 Karawang in knowing how much influence English Education in shaping the morals of students in SMK Negeri 1 Karawang. b. The results of this study can be used as information for educators in applying and knowing what factors are the biggest influence on the moral behavior of students in SMK Negeri 1 Karawang. c. As an evaluation material specifically for schools that carry out the learning process by teachers, and schools can monitor the morals of their students so that they are of good character. Keywords: English Education, Roles, Morals